Six Thinking Hats method as a means of functional literacy development - Irina N. Protopopova; Nadezhda A. Sytina (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The use of the 6 thinking hats method in a foreign language class as a means to develop functional literacy and universal training activities, which advance metasubject and personal results of learning, is presented in the article. The basic skills of the twenty-first century education are considered. Different approaches to understanding concepts such as “method” and “means” are analyzed and described. Various groups of methods for searching new ideas are distinguished, the type of the method is determined, as well as the method’s features and purposes of its application are defined in the article. The method was implemented in learning process in class activities on German language practical course. Based on the results of the conducted study and practical experiences of the method, it may be concluded that it is useful to use the 6 thinking hats method at a reflection stage of the training material content, as one of the technologies to develop competences (4 Cs), required to promote functional literacy.